Development of the Rodsim numerical simulator for the study of a sucker rod pump, comparing the Gibbs (1963) and Lea (1990) models - Cyrilo de Oliveira, Fernando; Romero, Oldrich Joel (Latin American Journal of Energy Research, 2024)
It is of great importance to be fully cognizant of the sucker rod pump system in order to make reliable production forecasts and to evaluate potential strategies for optimizing production processes. A frequently employed methodology in such circumstances is numerical simulation. A numerical sucker road pump simulator can provide valuable insights into production performance by generating dynamometric charts that represent the efficiency of this activity. Since the rod column behaves like a thin rod, it is possible to represent the mathematical model by a one-dimensional wave equation that describes the forces acting on this rod column. Lea (1990), proposing an improvement of the work of Gibbs (1963), considers the effects of the viscosity of the fluid produced in a vertical well without heat exchange, the piston diameter, the production column and the rods to obtain the damping factor, thus being more complete and producing a more accurate result in the dynamometric charts. Both models are implemented and discussed herein.The equations are discretized and solved in the Matlab® environment. The code includes a graphical user interface that generates the internal Rodsim application. The application is used to solve a typical case of a sucker rod pump and to obtain the surface and downhole dynamometric plots for certain scenarios.